CD103 Expression on Blastic Plasmacytoid Dendritic Cell Neoplasms in Peripheral Blood and Bone Marrow Samples - Ron Lee; Sally Ullery; Ron Thomason (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2020)
Blastic Plasmacytoid Dendritic Cell Neoplasm (BPDCN) is an aggressive neoplasm which is typically CD4+, CD56+, and CD123+. There is limited information regarding CD103 expression on blastic plasmacytoid dendritic cell neoplasms. We identified six cases of BPDCN and all six had at least partial CD103 expression (31-92% positive) with the majority having significant expression of CD103.